IMPACT OF DIGITALIZATION ON BEHAVIORAL ATTITUDES OF YOUTH: A SOCIOLOGICAL ANALYSIS - Kim Larisa Antonovna (Web of Journals Publishing, 2025)
The article discusses the characteristics of the digitalization process, the development trends of modern society, and identifies the features of the impact of digitalization of society on various aspects of life, including the formation of the value structure of consciousness of the younger generation.
Keywords: Digitalization, digital society, youth, society, values.